Serological epidemiology analysis of Cytomegalovirus infection in pregnant women in Diwaniyah, Iraq - Mohsen Abdul Khadhur Al-Zubaidi; Seyed Masoud Hosseini; Mohsen Abdul Nemah Al-Roudhan; Maather Baqer Hussein Al-Harmooshee (Iranian Journal of Microbiology)
Background and Objectives: Human cytomegalovirus (HCMV) infection is the most common cause of congenital infection during pregnancy. It is a major concern worldwide with a wide range of clinical outcomes in fetuses and newborns due to HCMV reactivation or reinfection during pregnancy. Primary maternal infection is best diagnosed by examining IgM and IgG antibodies. The current study aimed epidemiology survey of congenital HCMV infection in pregnant women in Diwaniyah. Materials and Methods: 600 blood samples were collected from pregnant women, between 18-45 years old, in Diwaniyah Governorate for 12 months, from January to December 2022, in regards to their place of residence (urban or rural). All samples were monitored for both IgG and IgM antibodies against HCMV using rapid test and ELISA. Results: Our findings showed a high positive rate for IgG (95.7%) and (96.2%) and a positive rate for IgM (1.5%) and (1.8%) for rapid test and ELISA, respectively. The highest IgG positive rate was in the age group 26-35 years (43.33%), while the lowest rate (13.0%) was in the age group 36-45 years. The HCMV infection rate in rural and urban areas were (96.48%) and (95.26%), respectively, with no significant differences (P value>0.05). Also, the rate of miscarriages among pregnant women infected with HCMV was 28.83%, and the highest infection rate (30.51%) was recorded in the age group 26-35 years. Conclusion: The prevalence of HCMV infection and its related miscarriage among the studied population is relatively high with the highest rate in the age group of 26-35 years.